Improved cyclobutyl nabilone analogs as potent CB1 receptor agonists - Papanastasiou, Ioannis P.; Georgiadis, Markos-Orestis; Iliopoulos-Tsoutsouvas, Christos; Paronis, Carol A.; Brust, Christina A.; Tran, Ngan K.; Ji, Lipin; Ma, Xiaoyu; Wood, JodiAnne T.; Zvonok, Nikolai; Tong, Fei; Bohn, Laura M.; et al. (European journal of medicinal chemistry, 2022)
In earlier work, we explored the SAR for the C3 side chain pharmacophore in the hexahydrocannabinol template represented by the drug nabilone, which resulted in the development of AM2389. In an effort for further optimization, we have merged features of nabilone and AM2389 and explored the C3 side chain with varying chain lengths and terminal substitutions. Of the compounds described here, a nabilone analog, AM8936, with the C6′-cyano-substituted side chain, was identified as the most successful analog capable of serving as a potential candidate for further development and a valuable tool for further in vivo studies. AM8936 behaved as a balanced and potent CB1 agonist in functional assays and was a potent and efficacious CB1 agonist in vivo. Our SAR studies are highlighted with the docking of AM8936 on the crystal structure of the hCB1 receptor. [Display omitted] •We explored the C3 side-chain in the hexahydrocannabinol template in terms of chain length and terminal substitution.•The cyclobutyl nabilone analog AM8936 with C6′ cyano-substitution was the most successful.•AM8936 behaved as a balanced and potent CB1 agonist in functional assays.•AM8936 behaved as a potent CB1 agonist in vivo.•Our structure activity relationships are highlighted via docking on the hCB1 crystal structure.